2017
DOI: 10.1007/s10955-017-1754-6
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Weakly Self-avoiding Walk with Contact Self-attraction

Abstract: We consider the critical behaviour of the continuous-time weakly self-avoiding walk with contact self-attraction on Z 4 , for sufficiently small attraction. We prove that the susceptibility and correlation length of order p (for any p > 0) have logarithmic corrections to mean field scaling, and that the critical two-point function is asymptotic to a multiple of |x| −2 . This shows that small contact self-attraction results in the same critical behaviour as no contact self-attraction; a collapse transition is p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the mathematical literature, it has been more common to model the polymer collapse transition in terms of the interacting self-avoiding walk in which a walk with a self-repulsion receives an energetic reward for nearest-neighbour contacts. A review of the literature on this model can be found in [den Hollander 2009, Chapter 6]; more recent papers include [Bauerschmidt et al 2017;Hammond and Helmuth 2019;Pétrélis and Torri 2018]. In our mean-field model set on the complete graph, there is no geometry, and the notion of collapse (a highly localised walk) is less meaningful.…”
Section: The Model and Resultsmentioning
confidence: 99%
“…In the mathematical literature, it has been more common to model the polymer collapse transition in terms of the interacting self-avoiding walk in which a walk with a self-repulsion receives an energetic reward for nearest-neighbour contacts. A review of the literature on this model can be found in [den Hollander 2009, Chapter 6]; more recent papers include [Bauerschmidt et al 2017;Hammond and Helmuth 2019;Pétrélis and Torri 2018]. In our mean-field model set on the complete graph, there is no geometry, and the notion of collapse (a highly localised walk) is less meaningful.…”
Section: The Model and Resultsmentioning
confidence: 99%
“…In [ 9 and ω 3 j (g 1/4 j ) 3 =g 3 j . This determined that we needed p N ≥ 9 + 1 = 10 derivatives of the field (see [14,Lemma 2.4]).…”
Section: B11 Norm Parametersmentioning
confidence: 99%
“…In the mathematical literature, it has been more common to model the polymer collapse transition in terms of the interacting self-avoiding walk in which a walk with a self-repulsion receives an energetic reward for nearest-neighbour contacts. A review of the literature on this model can be found in [den Hollander 2009, Chapter 6]; more recent papers include [Bauerschmidt et al 2017;Hammond and Helmuth 2019;Pétrélis and Torri 2018]. In our mean-field model set on the complete graph, there is no geometry, and the notion of collapse (a highly localised walk) is less meaningful.…”
Section: Mean-field Tricritical Polymers 169mentioning
confidence: 99%